If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + x = 12 + -12x Add '-12' to each side of the equation. 12 + -12 + x = 12 + -12 + -12x Combine like terms: 12 + -12 = 0 0 + x = 12 + -12 + -12x x = 12 + -12 + -12x Combine like terms: 12 + -12 = 0 x = 0 + -12x x = -12x Solving x = -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. x + 12x = -12x + 12x Combine like terms: x + 12x = 13x 13x = -12x + 12x Combine like terms: -12x + 12x = 0 13x = 0 Divide each side by '13'. x = 0 Simplifying x = 0
| 12gh+3g(2h+9)+3g= | | 8r^2+11r+3=0 | | 1-x^2-3x=0 | | -3(u-8)=6u-48 | | (2x-3)(x-2)=10 | | 4(x+2)+3(2x-5)=13 | | y=8.3(10)+479 | | M-14=-50 | | 1/25(16-4q)=8/25q-4/5 | | 4(2p-7)-(p+7)-2(p+6)=-77 | | G+5=-12 | | 6p=4p+2 | | 5x+5y+13=0 | | 48/22-25/5 | | -4[(3p+3)-(6p-1)]=8(5-p)-2 | | 4(q-2)+2(q+4)=6 | | -9n-5=-10n-12 | | 4(4z+4)-16(z+3)=-z-7(z+8) | | 12x-12=9x | | 4(4z+4)-16(z+3)=-z-(z+8) | | 6+3(x)=0 | | v+16=2v-20 | | K=-7+15 | | 3+3+3(-2)= | | (Ln(x))=5+x | | ln(x)=5+x | | 3+3+3x=0 | | p=96 | | 4cos^2(x)+4sin^2(2x)= | | -20x^2+75x+175=0 | | -3m-10=4m | | -13=n+-39 |